The effects of Cu-doping in V2O5 thin film cathode for microbattery - Nam, SC; Lim, YC; Park, HY; Jeon, EJ; Yoon, YS; Cho, WI; Cho, BW; Yun, KS (KOREAN INST CHEM ENGINEERS, 2001)
Copper-doped vanadium oxide (CuxV2O5) thin film cathode materials for a thin film microbattery have been prepared by DC reactive magnetron co-sputtering with O-2/Ar ratio of 10/90 and compared with pure V2O5 thin film. The film structures have been characterized by x-ray diffraction analysis, transmission electron microscopy, Auger electron spectroscopy and X-ray photoelectron spectroscopy, X-ray diffraction and TEM studies show that the CuxV2O5 film was amorphous and phenomenal behavior of copper present in thin film with substrate has been explained by thermodynamical model. Copper doping helps to increase the thickness of the film more than 1 micrometer resulting increase of total capacity. Cycling behavior of the CuxV2O5/Lipon/Li configuration cell system was beyond 500 cycles with average capacity of 50 mu Ah/cm(2)-mum, which is higher than the pure V2O5 thin film system.
Keywords: LITHIUM INTERCALATION; HOST MATERIALS; ELECTRODES; BATTERIES; XEROGELS; AEROGELS; COPPER